2020
DOI: 10.1002/adfm.201909756
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ordered Dual‐Mesoporous Polypyrrole/Graphene Nanosheets as Bi‐Functional Active Materials for High‐Performance Planar Integrated System of Micro‐Supercapacitor and Gas Sensor

Abstract: (1 of 9)Planar integrated systems of micro-supercapacitors (MSCs) and sensors are of profound importance for 3C electronics, but usually appear poor in compatibility due to the complex connections of device units with multiple mono-functional materials. Herein, 2D hierarchical ordered dual-mesoporous polypyrrole/graphene (DM-PG) nanosheets are developed as bi-functional active materials for a novel prototype planar integrated system of MSC and NH 3 sensor. Owing to effective coupling of conductive graphene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 67 publications
0
91
0
Order By: Relevance
“…Such macropores resulting from electrode roughness ensure the wetting of the electrode surface and fast ion diffusion at higher applied current, therefore ensuring a high rate performance [ 41 ]. Further, the evident micropores are highly significant for enhancing ion diffusion kinetics that improves the capacitance behavior of supercapacitors while contributing to the lower equivalent resistance [ 42 ]. Moreover, the total surface area and total percentage porosity of Ni 00 /NCO/RGO, Ni 10 /NCO/RGO, Ni 20 /NCO/RGO, and Ni 30 /NCO/RGO electrodes varies at ~17, ~92, ~16, ~16 m 2 /g and ~79, ~98, ~71, and ~70%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Such macropores resulting from electrode roughness ensure the wetting of the electrode surface and fast ion diffusion at higher applied current, therefore ensuring a high rate performance [ 41 ]. Further, the evident micropores are highly significant for enhancing ion diffusion kinetics that improves the capacitance behavior of supercapacitors while contributing to the lower equivalent resistance [ 42 ]. Moreover, the total surface area and total percentage porosity of Ni 00 /NCO/RGO, Ni 10 /NCO/RGO, Ni 20 /NCO/RGO, and Ni 30 /NCO/RGO electrodes varies at ~17, ~92, ~16, ~16 m 2 /g and ~79, ~98, ~71, and ~70%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is highly desirable to construct multifunctional materials that can work for all the devices involved. For instance, Qin et al 131 reported the synthesis of 2D hierarchically ordered dual-mesoporous Ppy/ graphene (DM-PG) nanosheets as bi-functional active materials for both MSC and NH 3 sensor (Fig. 6c).…”
Section: Energy Storagementioning
confidence: 99%
“…According to the laser technology in processing diversified micro-electrodes, the developed MSCs are easily integrated with other energy-related devices in widespread fields, showing great potential in practical intelligent application [215,231]. At present, laser-fabricated MSCs have been widely used in solar cells, photodetectors, sensors and generators [232].…”
Section: Integration and Application Of Laser-fabricated Mscsmentioning
confidence: 99%